ADHESION OF RUBBER TO METAL CORD AND ITS PTESETVATION - N. V. Andrianov; A. N. Savenok; A. A. Kravtsov; A. A. Ledneva (Литьë и металлургия, 2005)
It is shown that the correct selection of lubricant for wiredrawing allows not only to improve the technological characteristics of wire for the steel wire cord spin but to guarantee the stability of adhesion characteristics of steel wire cord as well.